Sosialisasi Produksi dan Strategi Pemasaran Olahan Ikan Bagi Istri Nelayan Majelis Taklim Alhidayah Oesapa Kupang - Muntasir Muntasir; Pius Weraman; Sri Prilmayanti Awaluddin; Nadra Aga Iryani (Yayasan Literasi Sains Indonesia, 2023)
The purpose of this Community Service is the socialization of diversified processed fish products and the marketing of the results. The priority problems of the fishing community in Oesapa Kupang, especially housewives and fishermen's wives, are the diversification of processed fish products that have a selling value, the importance of processing fish in the form of production of fish nuggets, fish jerky, and fish floss in increasing the income of fishermen's households. Methods of activities in the form of Education and Service to the Community by carrying out activities in work stages to facilitate implementation and evaluation, namely: 1. Activity Preparation Stage; 2. Activity Implementation Stage; 3. Activity Monitoring and Evaluation Stage. The results of the activity showed that the fishermen's wives who were also members of the Al Hidayah Oesapa Kupang religious assembly group had the motivation to increase their knowledge and skills in producing processed fish in the form of fish floss, fish nuggets, and fish jerky which were supported by evaluation results showing good ratings. From the results of this PKM activity, it was concluded that the outreach activities and marketing strategies for processed fish for fishermen's wives, the Taklim Assembly Group succeeded in motivating to produce processed fish in the form of fish floss, fish nuggets, fish jerky, and opened up income opportunities for fishermen's mothers or fishermen's wives. to market processed fish products. It needs the support of various parties to increase the diversification of processed fish and increase the income of Oesapa beach fishermen.